Neuronal response sto face-like and facial stimuli in the monkey superior colliculus - Nguyen, Minh Nui (2014)
The superficial layers of the superior colliculus (sSC) appear to function as a subcortical visual pathway that bypasses the striate cortex for the rapid processing of coarse facial information. We investigated the responses of neurons in the monkey sSC during a delayed non-matching-to-sample (DNMS) task in which monkeys were required to discriminate among five categories of visual stimuli [photos of faces with different gaze directions, line drawings of faces, face-like patterns (three dark blobs on a bright oval), eye-like patterns, and simple geometric patterns]. Of the 605 sSC neurons recorded, 216 neurons responded to the visual stimuli. Among the stimuli, face-like patterns elicited responses with the shortest latencies. Low-pass filtering of the images did not influence the responses. However, scrambling of the images increased the responses in the late phase, and this was consistent with a feedback influence from upstream areas. A multidimensional scaling (MDS) analysis of the population data indicated that the sSC neurons could separately encode face-like patterns during the first 25-ms period after stimulus onset, and stimulus categorization developed in the next three 25-ms periods. The amount of stimulus information conveyed by the sSC neurons and the number of stimulus-differentiating neurons were consistently higher during the 2nd to 4th 25-ms periods than during the first 25-ms period. These results suggested that population activity of the sSC neurons preferentially filtered face-like patterns with short latencies to allow for the rapid processing of coarse facial information and developed categorization of the stimuli in later phases through feedback from upstream areas.